KNOWLEDGE, ATTITUDE, AND PERCEPTION OF MEDICAL INTERNS TOWARDS ANTIMICROBIAL STEWARDSHIP IN A TERTIARY CARE HOSPITAL - P., MANSOOR BASHA; S., PADMA SRAVANI; S., SHARON SONIA (International Journal of Current Pharmaceutical Research, 2026)
Objective: To assess the knowledge, attitude, and perception of medical interns regarding antimicrobial stewardship programme in Government Medical College, Anathapuramu. Methods: A Cross-sectional, questionnaire-based study (KAP) was conducted in Medical Interns of 150 members in Government Medical College, Ananthapuramu. Only 128 medical interns participated in the study. The study was carried out between September 2025 and October 2025 among medical interns. Data entered and analysed using Statistical Package for Social Sciences (SPSS) software version 21.0 for Windows. Results: The total 128 interns are participated in a study in which males are about 42.2% and females are 57.8% Overall, interns showed good awareness and positive attitudes toward antimicrobial stewardship but suboptimal practices. This discrepancy underscores the need for structured training and real-world mentorship to translate knowledge into consistent stewardship behaviour. Conclusion: The current study demonstrates the dire need of medical interns for further education about antimicrobial stewardship. Hence, it is strongly recommended to provide a comprehensive, regular, standard and up-to-date educational training in all medical institutions, recommended to advocate curriculums and policies that build up antimicrobial stewardship programs. There is a critical need for structured education, training, and supervised clinical exposure to strengthen antimicrobial stewardship practices among medical interns.